Evaluation of the PathoTec „Rapid I-D System” - Blazevic, D. J. (1973)
The 10 biochemical test strips included in the PathoTec Rapid I-D System were evaluated for accuracy as compared to standard tests and for efficacy in identification of 193 gram-negative bacilli. The test agreement was 100% for oxidase and phenylalanine deaminase, 99% for indole, nitrate, and Voges-Proskauer, 98% for malonate, 97% for lysine decarboxylase, 90% for urease, 84% for H(2)S, and 75% for esculin hydrolysis. Most of the commonly isolated Enterobacteriaceae were identified correctly within 4 h. Errors in identification of Proteus morganii and P. rettgeri occurred because of positive H(2)S tests on the PathoTec strips with these organisms.